Churg-Strauss syndrome - Ilić Tatjana; Popović-Kuzmanović Dragana; Miličić Anka; Paranos Svetlana (Vojnosanitetski Pregled)
Churg-Strauss syndrome (CSS) is medium blood vessels vasculitis with predilection for lungs in patients with bronchial asthma, chronic eosinophilic pneumonia and positive ANCA in the sera in 55-67%. This is a case report of a 60 years old female patient with bronchial asthma, peripheral pulmonary infiltrations, blood eosinophilia, xerophtalmia, tachycardia, chronic rhino sinusitis, polyneuropathia and negative immunological tests: CIC (PEG), CRYO, ANA (IIF), RF (agglutination) and ANCA (IIF: pANCA and cANCA; ELISA: proteinase 3, lactoferrin, myeloperoxidase, elastase, cathepsin G). Eosinophilic infiltrates in the tissues tested by skin and salivary gland biopsies were not found. The patient had fulfilled five clinical diagnostic criteria and responded well to immunosuppressive therapy, so this case could be classified as the ANCA negative angiitis and granulomatous of CSS type.